Nordic responses to Covid-19: Governance and policy measures in the early phases of the pandemic - Saunes, Ingrid Sperre; Vrangbæk, Karsten; Byrkjeflot, Haldor; Jervelund, Signe Smith; Birk, Hans Okkels; Tynkkynen, Liina-Kaisa; Keskimäki, Ilmo; Sigurgeirsdóttir, Sigurbjörg; Janlöv, Nils; Ramsberg, Joakim; Hernández-Quevedo, Cristina; Merkur, Sherry; et al. (Health policy (Amsterdam), 2022)
•Declaration of emergency empowered central governance in Iceland, Finland and Norway.•Extended use of ad hoc experts group supplemented national advisory agencies.•Trust-based measures dominated, relying on peoples adherence to guidance.•Finland, Iceland and Norway had rigorous contact tracing from onset of pandemic.•Sweden had only regional pandemic preparedness plans. This paper explores and compares health system responses to the COVID-19 pandemic in Denmark, Finland, Iceland, Norway and Sweden, in the context of existing governance features. Content compiled in the Covid-19 Health System Response Monitor combined with other publicly available country information serve as the foundation for this analysis. The analysis mainly covers early response until August 2020, but includes some key policy and epidemiological developments up until December 2020. Our findings suggest that despite the many similarities in adopted policy measures, the five countries display differences in implementation as well as outcomes. Declaration of state of emergency has differed in the Nordic region, whereas the emphasis on specialist advisory agencies in the decision-making process is a common feature. There may be differences in how respective populations complied with the recommended measures, and we suggest that other structural and circumstantial factors may have an important role in variations in outcomes across the Nordic countries. The high incidence rates among migrant populations and temporary migrant workers, as well as differences in working conditions are important factors to explore further. An important question for future research is how the COVID-19 epidemic will influence legislation and key principles of governance in the Nordic countries.